Management of the Arabic Language Teaching Program for Non-Native Speakers - abdullah, maryam (Nurul Jadid University, 2023)
Arabic language teaching for non-native speakers plays a pivotal role in building linguistic competence and intercultural understanding, especially within Islamic educational institutions. This study aims to explore the management of Arabic language teaching programs for non-native speakers at the secondary school level, with a focus on MTsN 3 Nganjuk as a case study. The background of this research lies in the need for effective educational management that ensures Arabic language learning remains structured, goal-oriented, and responsive to student needs. Employing a qualitative descriptive approach, data were collected through interviews with Arabic teachers, observations of classroom activities, and documentation analysis related to teaching plans and evaluations. The findings reveal that successful program management is marked by clear planning, adaptive curriculum design, innovative teaching methods, and systematic evaluation strategies. Teacher competency, administrative support, and student-centered learning models also contribute to the effectiveness of the program. In practice, this study underscores the importance of integrated program management in enhancing student motivation, engagement, and Arabic language proficiency. The implications suggest that a well-managed teaching program can provide a sustainable model for Arabic language instruction tailored to the needs of non-native learners in the context of secondary madrasahs.